Energy transition, technological spillovers and elasticity of substitution - Chiara Colesanti Senni (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
Countries such as Germany and Switzerland have included the energy transition in their policy programs, setting specific targets in terms of energy production from renewables. However, the energy transition has a cost, which so far has been partly covered by subsidizing the clean production. This has produced an adverse effect, leading to overproduction in the clean sector and negative prices in the electricity spot market. An excessive subsidy, which does not takes into account technological spillovers and the elasticity of substitution, might be the cause. We use endogenous growth theory to study how the cost of the energy transition - proxied by a subsidy - is affected by these two channels. We provide a numerical solution to the model to give an insight into the magnitude of the effect considered. The main findings are: (1) technological spillovers reduce the cost of the energy transition and the subsidy becomes negative after a threshold value of relative spillover intensities; (2) a higher elasticity of substitution between the two sectors increases the cost of the energy transition.
Keywords: O33; O44; Q42; Q58; 330; Energy transition; Negative electricity prices; Technological spillovers; Elasticity of substitution; Market size effect